IMPLEMENTASI SISTEM PENDAFTARAN MENGGUNAKAN METODE MOORA UNTUK PENENTUAN KELAS BAGI PESERTA DIDIK BARU BERBASIS WEB - Izzatul Hamidi, M; Mashuri , Chamdan; Fatkhur Rizal , Muhammad (Inovate, 2024)
In the education process, increasing the quality offeducation is supported by severallfactors. One offthe factorssthat pushes towards improving the quality of education is how it is implemented or serviced, which includes: student readiness; availability of teaching staff; facilities and infrastructure. The new student selection activity is the first step to improvinggthe quality offeducation, namely determining the quality of input and decision making in the acceptance or selection of new students entering this class or group usinggthe Moora method. An estimation level with a base and exceptionally straightforward computation is easy to apply in the system and easy to apply in applications. A value calculation process is needed for the selection of new classes. The values used in the calculation include: average report cards, average uambn/usbk scores, average test scores, average achievement scores, and online exam selection results. The ranking results are obtained from the consequences of computations utilizing the Moora method using a sample of 5 studenttdata as a sample of the calculation, with the highest result being 7.4000 and the lowest result being 2.1000. After getting the calculation results, the class selection value is carried out based on the ranking results (yi) and entered into each class. Keywords: Moora Method, Ranking, Yi Value, Class Determination, New Student.